2007
DOI: 10.3928/1081-597x-20070501-03
|View full text |Cite
|
Sign up to set email alerts
|

Customized LASIK Treatment for Myopia Based on Preoperative Manifest Refraction and Higher Order Aberrometry: The Rochester Nomogram

Abstract: PURPOSE: To develop and test the efficacy of myopic treatment, based on preoperative manifest refraction and higher order aberrations, in enhancing the postoperative refractive error following customized LASIK treatment and compare results with the manufacturer-recommended sphere offset Zyoptix treatment nomogram, which does not account for the preoperative higher order aberrations. METHODS: One hundred seventy-five myopic eyes (89 patients) were treated based on the Rochester nomogram, which specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…It seems that the possibility of manually altering sphere and cylinder in wavefront systems could improve postoperative refractive accuracy. Our findings are in agreement with the conclusions in previous studies 6,7 in which the authors concluded that nomogram adjustments were needed to increase refractive accuracy in wavefront-guided ablations. In our study, the effect of including spherical aberration in the sphere calculation of the aberrometric refraction (Seidel method) was also evaluated.…”
Section: Discussionsupporting
confidence: 96%
“…It seems that the possibility of manually altering sphere and cylinder in wavefront systems could improve postoperative refractive accuracy. Our findings are in agreement with the conclusions in previous studies 6,7 in which the authors concluded that nomogram adjustments were needed to increase refractive accuracy in wavefront-guided ablations. In our study, the effect of including spherical aberration in the sphere calculation of the aberrometric refraction (Seidel method) was also evaluated.…”
Section: Discussionsupporting
confidence: 96%
“…These include optical zone size, 4,5 age, 4 and higher-order aberrations (HOAs). [6][7][8] We recently described a LASIK nomogram development method based on multiple regression analysis designed to take into account factors other than the attempted MRSE change. 3 Briefly, this approach derives a regression equation that can be used as for simple linear regression to steer percentage adjustments to overall treatment energy (%boost or deboost) based on the slope coefficient for the 4.0 mm pupil wavefront refraction spherical equivalent (WRSE); however, dioptric adjustments to the target sphere are calculated individually for each eye by subtracting the sum of the weighted additional factors plus the intercept constant from the multiple regression equation.…”
Section: Resultsmentioning
confidence: 99%
“…Based on good results from the Rochester nomogram, 16 we believed it would be important to consider the influence of higher-order Zernike terms. There is no simple way to include vector terms or polarity in a regression model.…”
Section: Discussionmentioning
confidence: 99%
“…Subbaram and MacRae 16,17 describe improved results for the Technolas PV (formerly Bausch & Lomb, Zyoptix) platform in myopic wavefront LASIK based on a proprietary nomogram developed using multiple regression analysis to provide a weighted adjustment to the treatment sphere that takes into account 3rd-order (coma) and 4th-order (spherical aberration) Zernike terms. Their published description is not full enough to allow other investigators to repeat their methods; however, their successful use of multiple regression analysis in wavefront LASIK nomogram development offers a way forward.…”
mentioning
confidence: 98%
See 1 more Smart Citation